Formação de imagens: aspectos quânticos e clássicos - Ivan Ferreira dos Santos (2006)
We have experimentally confirmed the theoretical predictions about the improvement of the resolution and apodization of images generated by simultaneous detection of photon pairs in momentum entangled state. This first work explores the differences between quantum imaging and classical coherent imaging. We verified that, in certain conditions, the same effects can also be obtained by using a mere classical incoherent source of light and detecting the intensity of light in the plane of the image. Moreover, we have performed two other studies. First, we have theoretically shown that it is possible to generate the image of a phase object via coincidence counting of photon pairs in an entangled state. Second, we performed another experiment where the improvement of resolution effects obtained with coincidence count of photons pairs in the entangled state can not be obtained by mere single counts of photons from an incoherent source. This second work explores the differences between quantum imaging and classical incoherent imaging. Motivated by the possibility of performing similar studies in the intense beam domain, we performed a third project: we experimentally studied the behavior of a selfimaging cavity (a device that could be useful to amplify the intensity of light carrying entangled photon pairs) when a non-linear crystal, that is capable to generated photons pairs in the entangled estate, is inserted inside of it.